2016
DOI: 10.1111/head.13010
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the Association Between Migraine, Pain, and Anxiety: Examining Migraine and Generalized Anxiety Disorders in a Canadian Population Based Study

Abstract: Generalized anxiety disorder is robustly associated with migraine and targeted outreach and interventions are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 73 publications
3
28
3
Order By: Relevance
“…Among men, anxiety was more strongly associated with diagnosed migraine than depression, a finding which is consistent with other work in the field. 41 Migraines are prevalent among individuals of white ethnicity, 11,45 a finding further corroborated by this study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Among men, anxiety was more strongly associated with diagnosed migraine than depression, a finding which is consistent with other work in the field. 41 Migraines are prevalent among individuals of white ethnicity, 11,45 a finding further corroborated by this study.…”
Section: Discussionsupporting
confidence: 81%
“…55 These findings align with other population health studies that show that headache-free individuals are more frequently in a relationship than those with headache/migraine. 57 While evidence shows that migraineurs are less likely to have someone they can rely on for important decision making, 41 we did not find an association between social support (MOS-SSS) and migraine prevalence in the present study. 29 Consistent with existing research, 29 we found higher social status to be related to lower odds of migraine for women after controlling for multiple measures of social support (eg, marital status, MOS-SSS) and other potential confounders (eg, SE, depressive symptoms).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Survey weights were computed by Statistics Canada, adjusted to a mean of 1 for analytical purposes, 36 and employed for reporting of proportions and statistical comparisons of respondent characteristics. Between-group descriptive comparisons using chi-square tests of independence and 2-tailed independent samples t-tests were conducted to explore characteristic differences between respondents whose parent reported health professionaldiagnosed migraine in the respondent and those who self-reported non-classified frequent headache.…”
Section: Methodsmentioning
confidence: 99%
“…No statistical power calculation was conducted prior to the study; the analyses were based on all available data. Survey weights were computed by Statistics Canada, adjusted to a mean of 1 for analytical purposes, 36 and employed for reporting of proportions and statistical comparisons of respondent characteristics. Regression-based techniques were unweighted.…”
Section: Methodsmentioning
confidence: 99%